EXPLORING PREFERRED LEADERSHIP STYLES ACROSS INDUSTRIES: PERSPECTIVES OF FOLLOWERS - Kerstin Ganzemiller; Phuong Vo; Andy Bertsch; Mohammad Saeed; James Ondracek; David Pellenwessel; Monica Kea; Elizabeth Nadeau (Universitas Gadjah Mada, 2021)
Introduction/ Main Objective: This study investigated preferred leadership styles, considered by many to be the most prevalent styles: autocratic, participative, and laissez-faire. We assessed ‘preferred leadership style’ from the perspective of the follower. The study aimed at exploring the variations in the preference for leadership styles across selected industries, namely the food/beverage industry, the retail industry, and the financial industry. Novelty: Leadership styles and perspectives have been investigated from divergent angles; but the preferred leadership styles have not been explored adequately across industries. This study endeavored at filling the gap in literature, and to provide direction to stakeholders, as regards followers’ perspectives.Research Methods: Our convenience sample was a result of a targeted effort to query respondents from three distinct samples: retail, restaurant/drink establishments, and consumer finance institutions (primarily banks). In addition to the preferred leadership from the perspective of the follower, we also collected demographic data including gender and age of the follower, in order to get the critical insights from demographic lenses. Our survey included the leader behavior questions that are borrowed from the LBDQ XII manual provided by Stogdill (1962), and involved an examination of the studies conducted by Van Eeden, et al.(2008) for examples of behaviors attributed to the various leadership styles.Finding/Results: Our results were mixed. In some analyses, our results were reflective of the literature. However, in other analyses, our results differed from the literature. The study evinced tolerance for autocratic leadership, particularly in retailing, much against the pre-conceived notion. Conclusion: The study confirmed the generally- accepted hypothesis that employees from the food/beverage industry, the retail industry, and the financial industry all prefer participative leadership significantly more than autocratic or laissez-faire styles.